A prospective multi-institutional study of eculizumab to treat high-risk stem cell transplantation–associated TMA - Jodele, Sonata; Dandoy, Christopher E.; Aguayo-Hiraldo, Paibel; Lane, Adam; Teusink-Cross, Ashley; Sabulski, Anthony; Mizuno, Kana; Laskin, Benjamin L.; Freedman, Jason; Davies, Stella M. (Blood, 2024)
•High-risk, untreated transplant-associated thrombotic microangiopathy after HCT has a dismal outcome due to multi-organ dysfunction.•Early therapy with the C5 blocker eculizumab significantly improved outcomes in patient with high-risk TA-TMA and attenuated organ dysfunction. [Display omitted] High-risk, complement mediated, untreated transplant-associated thrombotic microangiopathy (hrTMA) has dismal outcomes due to multi-organ dysfunction syndrome (MODS). The complement C5 blocker eculizumab shows promising results in hrTMA, but has not been prospectively studied in hematopoietic stem cell transplant (HCT) recipients. We performed the first multi-institutional prospective study in children and young adults to evaluate eculizumab as an early targeted intervention for hrTMA/MODS. We hypothesized that eculizumab would more than double survival in HCT recipients with hrTMA, compared to our prior study of prospectively screened, untreated hrTMAs serving as historical controls. HrTMA features (elevated terminal complement (sC5b-9) and proteinuria measured by random urine protein/creatinine ratio (≥1mg/mg)) were required for inclusion. The primary endpoint was survival at 6 six-months from hrTMA diagnosis. Secondary endpoints were cumulative incidence of MODS 6 months after hrTMA diagnosis and 1-year posttransplant survival. Eculizumab dosing included intensive loading, induction, and maintenance phases for up to 24 weeks of therapy. All 21 evaluated study subjects had MODS. Primary and secondary study endpoints were met by demonstrating survival of 71% (P < .0001) 6 months after hrTMA diagnosis and 62% 1 year after transplant. Of fifteen survivors, 11 (73%) fully recovered organ function and are well. Our study demonstrates significant improvement in survival and recovery of organ function in hrTMA using an intensified eculizumab dosing and real time biomarker monitoring. This study serves as a benchmark for planning future studies that should focus on preventative measures or targeted therapy to be initiated prior to organ injury. This trial was registered at www.clinicaltrials.gov as #NCT03518203. In the first prospective multicenter clinical trial to examine the role of anticomplement therapy with eculizumab in hematopoietic stem cell transplant–associated thrombotic microangiopathy (TMA), Jodele and colleagues demonstrate that high survival rates, 71% at 6 months, are achievable in children and young adults presenting with multiorgan dysfunction. These results are promising given prospectively collected historical control survival rates of 18% at the same time point. Further studies building on this biomarker-informed regimen are required to better understand how to utilize eculizumab, including before major organ dysfunction is manifest.